Molecular and structural architecture of polyQ aggregates in yeast - Gruber, Anselm; Lüchtenborg, Christian; Sachsenheimer, Timo; Brügger, Britta (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Huntington’s disease is caused by the expansion of a polyglutamine (polyQ) tract in the N-terminal exon of huntingtin (HttEx1), but the cellular mechanisms leading to neurodegeneration remain poorly understood. Here we present in situ structural studies by cryo-electron tomography of an established yeast model system of polyQ toxicity. We find that expression of polyQ-expanded HttEx1 results in the formation of unstructured inclusion bodies and in some cases fibrillar aggregates. This contrasts with recent findings in mammalian cells, where polyQ inclusions were exclusively fibrillar. In yeast, polyQ toxicity correlates with alterations in mitochondrial and lipid droplet morphology, which do not arise from physical interactions with inclusions or fibrils. Quantitative proteomic analysis shows that polyQ aggregates sequester numerous cellular proteins and cause a major change in proteome composition, most significantly in proteins related to energy metabolism. Thus, our data point to a multifaceted toxic gain-of-function of polyQ aggregates, driven by sequestration of endogenous proteins and mitochondrial and lipid droplet dysfunction.
Gesehen am 20.05.2019